EXPLORING THE FEASIBILITY OF CRIMINALISING MATERNAL SUBSTANCE ABUSE IN SOUTH AFRICA - Rinda Botha; Ramona Govender (Obiter, 2023)
With alcohol abuse by pregnant women being a significant problem in South Africa, particularly in the rural areas of the Western Cape province, the country carries one of the world’s heaviest burdens of foetal alcohol syndrome (FAS). FAS is regarded as the most severe of the foetal alcohol spectrum disorders. A child affected by FAS may suffer various developmental delays, including behavioural problems, poor language and fine motor skills, overall poor academic performance, mental retardation, and an increased tendency towards aggression and violence. Despite the alarming extent of the problem, maternal substance abuse is not currently a criminal offence in South Africa. This article explores the feasibility of criminalising maternal substance abuse, either by way of an amendment to the Children’s Act 38 of 2005 or by introducing a new statutory offence. As South African children are already afforded protection against abuse and neglect in terms of the Children’s Act, the prosecution of mothers who abuse substances while pregnant and then give birth to children suffering FAS-related harm could potentially also occur within this ambit. This would require an extension to the definitions of abuse and neglect in the Children’s Act and would have no effect on the legal status of a foetus in South Africa. Yet one would face certain challenges associated with the principle of legality: in terms of the ius strictum requirement, for instance, courts are expected to apply a strict rather than a broad interpretation to the definition of a crime. Therefore, if it is not provided for clearly enough in the definition of abuse and neglect, courts may be hesitant to include maternal substance abuse in their understanding of these crimes. Moreover, a strict interpretation of the meaning of “child” in the Children’s Act would exclude a foetus. In addition, a foetus does not possess legal subjectivity under South African law, which means that it generally does not have any legal rights, nor can it be the victim of any crime. Alternatively, the legislature could opt for introducing a new statutory offence to address maternal substance abuse separately. In this regard, criminalising maternal substance abuse as a materially-defined crime would be the best route to follow. This would restrict prosecution to instances where maternal substance abuse does in fact result in FAS-like effects in the child upon birth. In determining the feasibility of criminalising maternal substance abuse in South Africa, the article also takes a comparative look at United States law in this regard, particularly the position in Alabama and South Carolina. Developments in these states do seem to bode well for a decision to criminalise maternal substance abuse in South Africa as well. As shown in Hicks v State of Alabama 2014 153 So.3d 53 and Whitner v State 328 S.C. 1, 492 S.E.2d 777 (1997), maternal substance abusers in the United States may be prosecuted for either a specific statutory offence or general child neglect. However, while the courts in those cases imposed imprisonment, South Africa’s already overcrowded prisons coupled with the predominantly socio-economic causes of maternal substance abuse in the local context would warrant alternative sentencing options. These include referral to a rehabilitation centre or diversion. In addition, the United States courts seem to have accepted the view that foetuses should be afforded the same protection as children. As this would stir up a hornet’s nest in terms of the abortion debate and the legal status of a foetus in South Africa, following the American example in this respect is not recommended. However, this challenge can be overcome by criminalising maternal substance abuse as suggested above, by providing for prosecution only where the affected child is born alive and presents with FAS-like symptoms.